Más allá de la historia oficial. Escritura doméstica y claves secretas en las cartas de los conquistadores del Nuevo Mundo - Carmen Mena García (Caravelle)
The epistolary genre represents a source of historical information of extraordinary importance to reconstruct the complex world of mentalities as well as everyday life and social history in general. Here, we analyze some of the «messenger letters» written in Panama between 1524-1525 by the conquistadors themselves. In the same way, we present the encoded letter of Honduras’ treasurer, Rodrigo del Castillo, (León, Nicaragua, 1527), denoucing the abuses commited by Diego López de Salcedo, governor of Las Higueras and commanding officer in Honduras. At the same time, we ponder about the importance that criptographic genre had in the Indies’ epistolary history.